Crown recontouring with direct composites - Segarra, Armin G. (The Journal of the Philippine Dental Association)
This is a case of a 25 year old female complaining of an unesthetic smile. Crown recontouring with direct composite resin using the advanced stratification technique was done to transform the lateral incisor into a central incisor, giving the patient a more harmonious smile.